2018
DOI: 10.1002/jlb.5hi1117-446rr
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: Microbiota reconstitution restores intestinal integrity after cisplatin therapy

Abstract: Due to their cytotoxic activities, many anticancer drugs cause extensive damage to the intestinal mucosa and have antibiotic activities. Here, we show that cisplatin induces significant changes in the repertoire of intestinal commensal bacteria that exacerbate mucosal damage. Restoration of the microbiota through fecal-pellet gavage drives healing of cisplatin-induced intestinal damage. Bacterial translocation to the blood stream is correspondingly abrogated, resulting in a significant reduction in systemic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
71
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 25 publications
(37 reference statements)
1
71
0
3
Order By: Relevance
“…In more detail, they showed that the microbial gavage enhanced intestinal mucus production and the mobilization of CD11b+ myeloid cells into the mucosa. This in turn enhanced angiogenesis and healing of the cisplatin‐damaged intestinal tissues . With these findings, Perales‐Puchalt et al.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…In more detail, they showed that the microbial gavage enhanced intestinal mucus production and the mobilization of CD11b+ myeloid cells into the mucosa. This in turn enhanced angiogenesis and healing of the cisplatin‐damaged intestinal tissues . With these findings, Perales‐Puchalt et al.…”
mentioning
confidence: 83%
“…discovered that cisplatin therapy causes enhanced translocation of bacteria into the bloodstream which resulted in enhanced systemic inflammation (bacteremia). At the same time, alterations in the gastrointestinal microbial composition (dysbiosis) were induced in cisplatin treated tumor‐bearing mice . These results suggested that restoration of the pre‐cisplatin microbiome might reverse the therapy‐induced adverse effects.…”
mentioning
confidence: 90%
See 3 more Smart Citations